Dopamine and synaptic plasticity in the neostriatum - Gordon W. Arbuthnott; C.A. Ingham; Jeffery R. Wickens (2000)
After the unilateral destruction of the dopamine input to the neostriatum there are enduring changes in rat behaviour. These have been ascribed to the loss of dopamine and the animals are often referred to as 'hemiparkinsonian'. In the denervated neostriatum, we have shown that not only are the tyrosine hydroxylase positive boutons missing, but also the medium sized densely spiny output cells have fewer spines. Spines usually have asymmetric synapses on their heads. In a recent stereological study we were able to show that there is a loss of approximately 20% of asymmetric synapses in the lesioned neostriatum by 1 mo after the lesion. Current experiments are trying to establish the specificity of this loss. So far we have evidence suggesting that there is no obvious preferential loss of synapses from either D1 or D2 receptor immunostained dendrites in the neostriatum with damaged dopamine innervation. These experiments suggest that dopamine is somehow necessary for the maintenance of corticostriatal synapses in the neostriatum. In a different series of experiments slices of cortex and neostriatum were maintained in vitro in such a way as to preserve at least some of the corticostriatal connections. In this preparation we have been able to show that cortical stimulation results in robust excitatory postsynaptic potentials (EPSPs) recorded from inside striatal neurons. Using stimulation protocols derived from the experiments on hippocampal synaptic plasticity we have shown that the usual consequence of trains of high frequency stimulation of the cortex is the depression of the size of EPSPs in the striatal cell. In agreement with similar experiments by others, the effect seems to be influenced by NMDA receptors since the unblocking of these receptors with low Mg++ concentrations in the perfusate uncovers a potentiation of the EPSPs after trains of stimulation. Dopamine applied in the perfusion fluid round the slices has no effect but pulsatile application of dopamine, close to the striatal cell being recorded from, and in temporal association with the cortical trains, leads to a similar LTP like effect. The reduction of K+ channel conductance in the bath with TEA also has the effect of making cortical trains induce potentiation of corticostriatal transmission. TEA applied only to the cell being recorded from has no similar effect; the cortical stimulation again depresses the EPSP amplitude, so the site of action of TEA may well be presynaptic to the striatal cell. The morphological and physiological experiments may not necessarily be related but it is tempting to suggest that dopamine protects some corticostriatal synapses by potentiating them but that in the absence of dopamine others simply disconnect and are no longer detectable on electron microscopy.